Recurrent X chromosome-linked deletions: discovery of new genetic factors in male infertility. Issue 5 (13th January 2014) - Lo Giacco, D; Chianese, C; Ars, E; Ruiz-Castañé, E; Forti, G; Krausz, C
Abstract : Background: The role of X-linked genes and copy-number variations (CNVs) in male infertility remains poorly explored. Our previous array-CGH analyses showed three recurrent deletions in Xq exclusively (CNV67) and prevalently (CNV64, CNV69) found in patients. Molecular and clinical characterisation of these CNVs was performed in this study. Methods: 627 idiopathic infertile patients and 628 controls were tested for each deletion with PCR+/−. We used PCR+/− to map deletion junctions and long-range PCR and direct sequencing to define breakpoints. Results: CNV64 was found in 5.7% of patients and in 3.1% of controls (p=0.013; OR=1.89; 95% CI 1.1 to 3.3) and CNV69 was found in 3.5% of patients and 1.6% of controls (p=0.023; OR=2.204; 95% CI 1.05 to 4.62). For CNV69 we identified two breakpoints, types A and B, with the latter being significantly more frequent in patients than controls (p=0.011; OR=9.19; 95% CI 1.16 to 72.8). CNV67 was detected exclusively in patients (1.1%) and was maternally transmitted. The semen phenotype of one carrier (11-041) versus his normozoospermic non-carrier brother strongly indicates a pathogenic effect of the deletion on spermatogenesis. MAGEA9, an ampliconic gene reported as independently acquired on the human X chromosome with exclusive physiological expression in the testis, is likely to be involved in CNV67. Conclusions: We provide the first evidence for X chromosome-linked recurrent deletions associated with spermatogenic impairment. CNV67, specific to spermatogenic anomaly and with a frequency of 1.1% in oligo/azoospermic men, resembles the AZF regions on the Y chromosome with potential clinical implications.